An assessment of aggregate quality from crusher plant as construction material used in Kaski district of Nepal - Banstola, Ramesh; GC, Santosh (Journal of Engineering Issues and Solutions, 2023)
Quality refers to the minimum acceptable physical dimensional characteristics as specified in the form of a specification. Quality improvements are essential for any crusher plant or entrepreneur to stay in operation in a competitive business. Aggregates have a significant relation with the strength of the various grades of concrete to optimize the quality and obtain the specific result on the strength of concrete. The aggregate properties play significant role to enhance quality of concrete and its durability. Among various properties of the aggregate, only physical and mechanical properties of coarse and fine aggregates were tested and evaluated. Results showed that coarse and fine aggregates of the crusher plants A, B, and C lie within the specifications defined by standard specifications for road and bridge works - 2073 (with second amendment 2078) of Department of Roads (DoR), Nepal, and the plants of D, E, F, G, H, I, and J does not comply with the standard. The physical and mechanical properties of aggregates complying with the standard help gain strength, durability, and other properties of concrete in concrete mix design.